Steel-polymer fiber continuous composite fiber reinforced alkali-activated volcanic ash concrete
By using steel-polymer fiber continuous composite fibers in alkali-excited volcanic ash concrete, the problem of insufficient corrosion resistance and durability of traditional steel fibers in high corrosion environments is solved, and high toughness, durability and low-cost concrete materials are achieved , suitable for marine construction projects.
Patent Information
- Application Number
- CN202411536506.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional steel fibers have poor corrosion resistance and durability in complex environments with high corrosion, making it difficult to meet the requirements of marine construction projects for high toughness, durability and low cost.
Steel-polymer fiber continuous composite fiber is used to treat, wrap carbon fiber wires through impregnation, and coat with molten active ceramic coating to form steel-polymer fiber continuous composite fibers and incorporate into alkali-excited volcanic ash concrete.
It significantly improves the tensile strength and crack resistance of concrete, adapts to harsh and complex environments, and improves durability performance, ensuring that concrete evenly transmits load under load, avoids stress concentration, and improves compressive strength and integrity.
Smart Images

Figure CN119390400A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to a method for preparing a steel-polymer fiber continuous composite fiber reinforced alkali-activated volcanic ash concrete material. Background Art
[0002] In marine construction projects, there is often a lack of fresh water, coarse aggregate, fine aggregate and other materials required for construction. However, using local materials and finding suitable building material substitutes can avoid high ocean transportation costs, shorten project construction period, and bring considerable economic benefits and social value to marine project construction.
[0003] Alkali-activated volcanic ash is a green and environmentally friendly material that can reduce the carbon dioxide released by cement production. Volcanic ash is abundant on land, especially in marine areas, and can be obtained locally. Due to its own properties, it can be activated by alkali to bring out its potential activity. However, alkali-activated concrete shrinks and cracks greatly, so it is necessary to improve the mechanical properties of alkali-activated volcanic ash concrete by adding fibers. However, due to the poor corrosion resistance and durability of traditional steel fibers, it is necessary to develop a high-performance concrete material that can be used in highly corrosive and complex environments, has high toughness, durability, and low cost. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a steel-polymer continuous composite fiber reinforced alkali-activated volcanic ash concrete material in view of the deficiencies of the above-mentioned prior art. The tensile strength and crack resistance of the material are greatly improved, and the material is effectively adapted to various harsh and complex engineering environments, and the durability is significantly improved. In addition, the steel-polymer continuous composite fiber is well bonded to the concrete matrix, which can ensure that when the concrete is subjected to external loads, the load can be evenly transferred, avoiding stress concentration inside the concrete and causing damage, and greatly improving the compressive strength of the concrete and the integrity of the structural components.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolan concrete material, the method comprising:
[0006] S1, performing a resin dipping treatment on steel fibers to obtain resin-impregnated steel fibers, and then winding carbon fiber filaments on the resin-impregnated steel fibers to obtain wound composite fibers;
[0007] S2, coating the surface of the wound composite fiber obtained in S1 with a molten active ceramic coating to obtain a coated steel-polymer fiber continuous composite fiber;
[0008] S3, placing the coated steel-polymer fiber continuous composite fiber obtained in S2 in a dry environment for drying, and then curing it at a temperature of 80° C. for 6 hours, and cutting it to obtain the steel-polymer fiber continuous composite fiber;
[0009] S4. Add coarse aggregate, natural volcanic ash, fine aggregate and the steel-polymer continuous composite fiber obtained in S3 in sequence, mix and stir for 3 minutes, add a water reducer and an activator while stirring, pour into a mold for standard curing and specified testing, and obtain a steel-polymer continuous composite fiber reinforced alkali-activated volcanic ash concrete material.
[0010] Preferably, the active ceramic coating in S2 is made of the following raw materials in mass fractions: P2O5 24.1%, Al2O3 15.8%, Na2O 12.1%, K2O 11.5%, B2O3 9.4%, CaF2 6.4%, Li2O 6.1%, SiO2 5.8%, CaO 3.4%, NiO 2.3%, CoO 1.7%, and ZrO2 1.4%.
[0011] Preferably, the length of the steel-polymer fiber continuous composite fiber in S3 is 10 mm to 40 mm.
[0012] Preferably, the coarse aggregate in S4 is crushed stone; the fine aggregate is river sand; the water reducer is a polycarboxylate water reducer; and the activator is a mixture of NaOH solution and water glass.
[0013] Preferably, the mass ratio of the coarse aggregate, natural volcanic ash, fine aggregate, steel-polymer fiber continuous composite fiber, water reducer and activator in S4 is (900-1000): (350-420): (480-570): (11-20): (3-14): (130-240).
[0014] Preferably, the cube compressive strength of the steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolanic concrete material in S4 is higher than C40 after curing for 28 days.
[0015] Compared with the prior art, the present invention has the following advantages:
[0016] 1. The present invention composites carbon fiber filaments and steel fibers into steel-polymer fiber continuous composite fibers, and coats the surface with active enamel and mixes it into alkali-activated volcanic ash concrete (composed of coarse aggregate, natural volcanic ash, fine aggregate, water reducer and activator). The present invention adds steel-continuous fiber composite fibers for application in highly corrosive and complex environments, and has high toughness and durability as well as low cost.
[0017] 2. The tensile strength and crack resistance of the steel-polymer fiber continuous composite fiber reinforced alkali-activated volcanic ash concrete material prepared by the present invention are greatly improved, and it is effectively adapted to various harsh and complex engineering environments, and the durability is significantly improved. In addition, the steel-polymer fiber continuous composite fiber is well bonded to the concrete matrix, which can ensure that when the concrete is subjected to external loads, the load can be evenly transferred, avoiding stress concentration inside the concrete and causing damage, and greatly improving the compressive strength of the concrete and the integrity of the structural components.
[0018] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a diagram of the steel-polymer fiber continuous composite fiber prepared in step S3 of Example 1 of the present invention.
[0020] Figure 2 It is a schematic diagram of the steel-polymer fiber continuous composite fiber prepared in step S3 of Example 1 of the present invention.
[0021] Figure 3 1 and 2 are stress-strain curves of Example 1 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0022] Example 1
[0023] The preparation method of the steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolan concrete material of this embodiment is as follows:
[0024] S1, performing a resin dipping treatment on steel fibers to obtain resin-impregnated steel fibers, and then winding carbon fiber filaments on the resin-impregnated steel fibers to obtain wound composite fibers;
[0025] Steel fiber was purchased from Hebei Zhifeng Rubber & Plastic Products Co., Ltd., and was a shear-type steel fiber with a length of 35 mm, a thickness of 0.2 mm, and an equivalent diameter of 1.2 mm; carbon fiber was purchased from Shenzhen Guosen Linghang Technology Co., Ltd., and the model was HEXCEL AS4C-GP 3K;
[0026] S2. The surface of the wound composite fiber obtained in S1 is coated with a molten active ceramic coating to obtain a coated steel-polymer fiber continuous composite fiber; the active ceramic coating is made of the following raw materials in mass fraction: P2O5 (24.1%), Al2O3 (15.8%), Na2O (12.1%), K2O (11.5%), B2O3 (9.4%), CaF2 (6.4%), Li2O (6.1%), SiO2 (5.8%), CaO (3.4%), NiO (2.3%), CoO (1.7%), ZrO2 (1.4%); the active ceramic coating material is melted at high temperature and coated on the surface of the steel fiber to form a dense protective layer on the surface of the steel fiber, thereby achieving the purpose of enhancing the corrosion resistance of the steel fiber and the bonding strength with concrete;
[0027] The active porcelain coating material is an inorganic non-metallic material based on phosphate aluminate. B2O3 and CaF2 in the raw materials can play a role in flux; transition metal oxides NiO and CoO can improve the adhesion of the porcelain glaze; ZrO2 can improve the alkali resistance of the porcelain glaze so that it can be used in the alkaline environment of concrete.
[0028] S3, placing the coated steel-polymer fiber continuous composite fiber obtained in S2 in a dry environment for drying, and then curing it at a temperature of 80° C. for 6 hours, and cutting it to obtain a steel-polymer fiber continuous composite fiber with a length of 10 mm to 40 mm; the prepared steel-polymer fiber continuous composite fiber is as follows Figure 1 As shown;
[0029] Figure 2 Schematic diagram of the steel-polymer fiber continuous composite fiber prepared in step S3, wherein (a) is an overall view; (b) is a cross-sectional view (cross section), in which 1 represents an active enamel coating, 2 represents carbon fiber filaments, and 3 represents steel fibers).
[0030] S4, sequentially add coarse aggregate (crushed stone), natural volcanic ash, fine aggregate (river sand) and the steel-polymer continuous composite fiber obtained in S3, mix and stir for 3 minutes, add a water reducer (polycarboxylic acid water reducer) and an activator (a mixture of NaOH solution and water glass) while stirring, and pour into a mold for standard curing and specified testing to obtain a steel-polymer continuous composite fiber reinforced alkali-activated volcanic ash concrete material; the mass ratio of the coarse aggregate, natural volcanic ash, fine aggregate, steel-polymer continuous composite fiber, water reducer and activator is 961:420:517:14.3:9:189; the activator is a mixture of NaOH solution and water glass in a mass ratio of 2.4:1, wherein the concentration of the NaOH solution is 8 mol / L;
[0031] In this embodiment, coarse aggregate, natural volcanic ash and fine aggregate are first put into a mixer in this order and dry stirred for 3 minutes. During this process, steel-polymer continuous composite fiber is gradually added to avoid fiber agglomeration and ensure that the mixture is uniform and the fibers are well dispersed. After all the raw materials are fully stirred, the activator with a water reducer is slowly poured in while stirring, and finally poured.
[0032] The slump and mechanical strength of the steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolan concrete prepared in this example are shown in Table 1.
[0033] Table 1 Performance test of steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolan concrete in Example 1
[0034]
[0035] The cube compressive strength of the steel-polymer continuous composite fiber reinforced alkali-activated volcanic ash concrete material prepared in Example 1 is 47.6 MPa after curing for 28 days, which is higher than C40 (the standard value of the cube compressive strength of concrete reaches 40 MPa).
[0036] The steel-polymer fiber continuous composite fiber prepared in this embodiment is obtained by winding carbon fibers with high specific strength and strong corrosion resistance on the surface of the steel fiber, and then coating it with a molten active porcelain coating. The active porcelain coating is an inorganic material based on phosphate aluminate, which has good anti-aging properties and will not experience obvious performance aging after long-term use; it has low sensitivity to damage and can "self-repair" when slightly damaged. At the same time, since the active calcium silicate of the active porcelain coating can undergo hydration reaction, it provides a more uniform transition at the interface between it and the concrete, achieving a close combination of the active porcelain coating and the concrete surface. Therefore, in summary, the steel-polymer fiber continuous composite fiber reinforced alkali-activated volcanic ash concrete of the present invention can be used in highly corrosive and complex environments, and has both high toughness and durability.
[0037] The steel-polymer fiber continuous composite fiber reinforced alkali-activated volcanic ash concrete prepared in this embodiment has greatly improved tensile strength and crack resistance, effectively adapts to various harsh and complex engineering environments, and significantly improves durability. In addition, the steel-polymer fiber continuous composite fiber is well bonded to the concrete matrix, which can ensure that when the concrete is subjected to external loads, the load can be evenly transferred to avoid stress concentration inside the concrete and damage, and the compressive strength of the concrete and the integrity of the structural components are greatly improved.
[0038] Comparative Example 1
[0039] This comparative example is a method for preparing ordinary steel fiber reinforced alkali-activated pozzolanic concrete, which is:
[0040] The mix design of concrete is carried out according to the standard, and the required materials are accurately weighed, 420 parts of natural volcanic ash, 189 parts of activator (same as the activator in Example 1), 517 parts of fine aggregate (river sand), 961 parts of coarse aggregate (crushed stone), 9 parts of polycarboxylic acid water reducer, and 14.3 parts of steel fiber. Put them into the mixer in the order of coarse aggregate, natural volcanic ash, and fine aggregate and stir for 3 minutes. In this process, steel fiber is gradually added to avoid fiber agglomeration, ensure that the mixture is uniform, and the fiber is well dispersed. After all the raw materials are fully stirred, slowly pour the water reducer and activator while stirring, and pour them into the mold for standard maintenance and specified testing.
[0041] The slump and mechanical strength of the ordinary steel fiber reinforced alkali-activated pozzolan concrete prepared in this comparative example are shown in Table 2. The test results show that compared with Example 1, the cube compressive strength, prism compressive strength, splitting tensile strength and flexural strength of the steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolan concrete prepared in Example 1 after 28 days are increased by 7.25%, 8.65%, 6.13% and 5.04% respectively. From the stress-strain curve ( Figure 3 ) The ductility of the steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolan concrete (Example 1) obtained is better than that of the steel fiber reinforced alkali-activated pozzolan concrete (Comparative Example 1).
[0042] Table 2 Performance test of ordinary steel fiber reinforced alkali-activated pozzolan concrete in comparative example 1
[0043]
[0044] Comparative Example 2
[0045] This comparative example is a method for preparing ordinary carbon fiber reinforced alkali-activated pozzolan concrete, which is:
[0046] The mix design of concrete is carried out according to the standard, and the required materials are accurately weighed, 420 parts of natural volcanic ash, 189 parts of activator (same as the activator in Example 1), 517 parts of fine aggregate (river sand), 961 parts of coarse aggregate (crushed stone), 9 parts of polycarboxylic acid water reducer, and 0.57 parts of carbon fiber (the amount is the same as the carbon fiber wound in the steel-polymer fiber continuous composite fiber in Example 1). Put it into the mixer in the order of coarse aggregate, natural volcanic ash, and fine aggregate and stir for 3 minutes. In this process, carbon fiber is gradually added to avoid fiber agglomeration, ensure that the mixture is uniform, and the fiber is well dispersed. After all the raw materials are fully stirred, the water reducer and activator are slowly poured in while stirring, and it is poured into the mold for standard maintenance and specified testing.
[0047] The slump and mechanical strength of the ordinary carbon fiber reinforced alkali-activated volcanic ash concrete prepared in this comparative example are shown in Table 3. The test results show that compared with Example 1, the cube compressive strength, prism compressive strength, splitting tensile strength and flexural strength of the steel-polymer fiber continuous composite fiber reinforced alkali-activated volcanic ash high-performance concrete prepared in Example 1 increased by 14.93%, 13.22%, 10.33% and 10.93% at 28 days respectively. From the stress-strain curve ( Figure 2 ) The ductility of the steel-polymer fiber continuous composite fiber reinforced alkali-activated volcanic ash high performance concrete (Example 1) obtained is better than that of the carbon fiber reinforced alkali-activated volcanic ash concrete (Comparative Example 2).
[0048] Table 3 Performance test of ordinary carbon fiber reinforced alkali-activated pozzolan concrete in comparative example 2
[0049]
[0050] Comparative Example 3
[0051] The preparation method of the ordinary alkali-activated pozzolan concrete of this comparative example is as follows:
[0052] The concrete mix ratio is designed according to the standard, and the required materials are accurately weighed, including 420 parts of natural volcanic ash, 189 parts of activator (same as the activator in Example 1), 517 parts of fine aggregate (river sand), 961 parts of coarse aggregate (crushed stone), and 9 parts of polycarboxylate water reducer. The coarse aggregate, natural volcanic ash, and fine aggregate are put into the mixer in the order of dry stirring for 3 minutes to ensure that the mixture is uniform. After all the raw materials are fully stirred, the water reducer and activator are slowly poured in while stirring, and the mixture is poured into the mold for standard curing and specified testing.
[0053] The slump and mechanical strength of the ordinary alkali-activated pozzolan concrete prepared in this comparative example are shown in Table 4. The test results show that compared with the ordinary alkali-activated pozzolan concrete specimens, the 28-day compressive strength, splitting tensile strength and flexural strength of the steel-polymer continuous composite fiber reinforced alkali-activated pozzolan concrete increased by 17.97%, 21.93%, 16.52% and 15.43% respectively. From the stress-strain curve ( Figure 2 ) The ductility of the steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolan concrete is significantly better than that of ordinary alkali-activated pozzolan concrete (Comparative Example 3).
[0054] Table 4 Performance test of ordinary alkali-activated pozzolan concrete of comparative example 3
[0055]
[0056] Example 2
[0057] The preparation method of the steel-polymer continuous composite fiber reinforced alkali-activated volcanic ash concrete material of this embodiment is the same as that of Example 1, except that the mass ratio of the coarse aggregate, natural volcanic ash, fine aggregate, steel-polymer continuous composite fiber, water reducer and activator in step S4 is 900:420:480:20:8:240.
[0058] Table 5 Performance test of steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolan concrete in Example 2
[0059]
[0060] The cube compressive strength of the steel-polymer fiber continuous composite fiber reinforced alkali-activated volcanic ash concrete material prepared in Example 2 is 49.3 MPa after curing for 28 days, which is higher than C40 (the standard value of the cube compressive strength of concrete reaches 40 MPa).
[0061] Example 3
[0062] The preparation method of the steel-polymer continuous composite fiber reinforced alkali-activated volcanic ash concrete material of this embodiment is the same as that of Example 1, except that the mass ratio of the coarse aggregate, natural volcanic ash, fine aggregate, steel-polymer continuous composite fiber, water reducer and activator in step S4 is 1000:400:570:20:14:240.
[0063] Table 6 Performance test of steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolan concrete in Example 3
[0064]
[0065] The cube compressive strength of the steel-polymer continuous composite fiber reinforced alkali-activated volcanic ash concrete material prepared in Example 3 was 46.5 MPa after curing for 28 days, which was close to C40 (the standard value of the cube compressive strength of concrete reached 40 MPa).
[0066] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolan concrete material, characterized in that: The method is: S1, performing a resin dipping treatment on steel fibers to obtain resin-impregnated steel fibers, and then winding carbon fiber filaments on the resin-impregnated steel fibers to obtain wound composite fibers; S2, coating the surface of the wound composite fiber obtained in S1 with a molten active ceramic coating to obtain a coated steel-polymer fiber continuous composite fiber; S3, placing the coated steel-polymer fiber continuous composite fiber obtained in S2 in a dry environment for drying, and then curing it at a temperature of 80° C. for 6 hours, and cutting it to obtain the steel-polymer fiber continuous composite fiber; S4. Add coarse aggregate, natural volcanic ash, fine aggregate and the steel-polymer continuous composite fiber obtained in S3 in sequence, mix and stir for 3 minutes, add a water reducer and an activator while stirring, pour into a mold for standard curing and specified testing, and obtain a steel-polymer continuous composite fiber reinforced alkali-activated volcanic ash concrete material.
2. The method for preparing a steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolanic concrete material according to claim 1, characterized in that: The active ceramic coating described in S2 is made of the following raw materials in mass fraction: P2O5 24.1%, Al2O3 15.8%, Na2O 12.1%, K2O 11.5%, B2O3 9.4%, CaF2 6.4%, Li2O 6.1%, SiO2 5.8%, CaO 3.4%, NiO 2.3%, CoO 1.7%, and ZrO2 1.4%.
3. The method for preparing a steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolanic concrete material according to claim 1, characterized in that: The length of the steel-polymer fiber continuous composite fiber in S3 is 10 mm to 40 mm.
4. The method for preparing a steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolan concrete material according to claim 1, characterized in that: In S4, the coarse aggregate is crushed stone; the fine aggregate is river sand; the water reducer is polycarboxylate water reducer; and the activator is a mixture of NaOH solution and water glass.
5. The method for preparing a steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolanic concrete material according to claim 1 or 4, characterized in that: The mass ratio of the coarse aggregate, natural volcanic ash, fine aggregate, steel-polymer continuous composite fiber, water reducer and activator in S4 is (900-1000): (350-420): (480-570): (11-20): (3-14): (130-240).
6. The method for preparing a steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolanic concrete material according to claim 1, characterized in that: The cube compressive strength of the steel-polymer fiber continuous composite fiber reinforced alkali-activated pozzolanic ash concrete material described in S4 is higher than that of C40 after curing for 28 days.
Citation Information
Cited By
Preparation process of bending-tensile concrete
CN120056242A